Características pós abate de novilhos Braford recebendo crescentes níveis de milho grão inteiro na dieta - Borchate, Daniele (2020)
The aim of this study was to evaluate the effect of increasing levels of whole maize on the carcass and non-carcass characteristics of new volume-fed Braford steers. A total of 44 Braford steers were distributed in four controls, in a randomized open design, with 11 animals in each. The controls consisted of four diets composed of different levels of whole corn kernels, thus: 62.5, 75, 87.5 and 100 g kg-1, of whole grain corn to replace corn silage. The cattle were confined with an initial average weight and age of 293.31 ± 36.24 kg and 13.5 months, respectively. They were slaughtered with approximately 420 kg of body weight. After the slaughter of unmeasured items or the yield of components not belonging to the carcass, quantitative and qualitative characteristics of the carcass and yield of primary cuts. There are no differences for the weight of the empty body, the weight of the hot and cold carcass, the variations of the carcass and primary cuts and the tissue composition. The thickness of subcutaneous fat was lower for the highest level of corn in the diet. Marbling was similar between diets. The heart was the only vital organ to present statistical statistics, as well as the blood variable. Cavity fats were not affected by the treatments. You can get more heavy weights to apply with greater volume, unlike the intestines, which were heavier with increased corn in the diet. The increase in the inclusion of whole corn in the diet of Braford steers does not alter the quantitative and qualitative characteristics of the carcass and empty body weight.